Breaking the Web Barriers of the e-Administration Using an Accessible Digital Certificate Based on a Cryptographic Token. (14th September 2015) - García, Boni; Gómez, Ana; Conde, Rafael; Hernández, Yolanda; Valero, Miguel Ángel
Abstract : The purpose of developing e-Government is to make public administrations more efficient and transparent and to allow citizens to more comfortably and effectively access information. Such benefits are even more important to people with a physical disability, allowing them to reduce waiting times in procedures and travel. However, it is not in widespread use among this group, as they not only harbor the same fears as other citizens, but also must cope with the barriers inherent to their disability. This research proposes a solution to help persons with disabilities access e-Government services. This work, in cooperation with the Spanish Federation of Spinal-Cord Injury Victims and the Severely Disabled, includes the development of a portal specially oriented towards people with disabilities to help them locate and access services offered by Spanish administrations. Use of the portal relies on digital authentication of users based on X.509, which are found in identity cards of Spanish citizens. However, an analysis of their use reveals that this feature constitutes a significant barrier to accessibility. This paper proposes a more accessible solution using a USB cryptographic token that can conceal from users all complexity entailed in access to certificate-based applications, while assuring the required security.